Shear-Induced Platelet Aggregation in Normal Subjects and Stroke Patients - Konstantopoulos, Konstantinos; Grotta, James C; Sills, Cynthia; Wu, Kenneth K; David Heliums, J (Thrombosis and Haemostasis, 1995)
Elevated levels of shear stress that occur in stenotic arteries may induce platelet aggregation and initiate thrombosis. Shear-induced platelet aggregation (SIPA) was studied in groups of ischemic stroke patients and normal subjects using a viscometric-flow cytometric technique. Twenty-three patients who sustained an ischemic stroke that was not of cardiac origin were included in this study, and were classified either as atherosclerotic (n = 15) or as lacunar (n = 8) stroke patients. The results show that shear stresses at the levels which occur in arteries partially occluded by atherosclerosis or vascular spasm strongly activate and aggregate platelets, and this response is much more pronounced in non-lacunar stroke patients who had documented atherosclerotic disease of their cerebral vessels. SIPA is not affected by the time of blood drawing after the onset of stroke suggesting that these platelet abnormalities are not transient but chronic. Furthermore, the extent of platelet activation detected by an anti-P-selectin monoclonal antibody and the proportion of neutrophil-platelet aggregates circulating in vivo are significantly higher in the atherosclerotic stroke patients studied at least one month after the onset of stroke. The results indicate that the enhanced platelet responses observed in atherosclerotic stroke patients are not consequences of ischemia, and therefore both platelet activation and elevated SIPA may be considered as important risk factors for stroke. The methodology developed in this work may be useful for characterization of platelet reactivity, and may contribute to our understanding of thrombotic mechanisms.